Strategy and communication for innovation : integrative perspectives on innovation in the digital economy - Pfeffermann, Nicole; Gould, Julie (Springer, 2017)
Innovation is a continuous dialog. This dialog has reached a new dimension in the digitalized information age. The necessity of managing strategic collaboration activities and information flows within and across organizations led thereby to a new thinking in management. As a result, both strategy and communication are important drivers of innovation and growth and, hence, critical factors underpinning sustainable innovation and market success in the long-run. As a new communication field, innovation communication facilitates managing open innovation, strengthening corporate culture and reputation, successfully launching new products and services as well as building new capabilities and difficult-to-imitate resources. Consequently, firms today need to develop a strong communication portfolio as an integral part of any information-innovation processes on a functional and/or company-wide level. This also includes understanding the role of communicators in clusters, research networks, and supportive ecosystems. The third edition of the contributed volume "Strategy and Communication for Innovation" concentrates on emerging approaches and methods for integrating communication in corporate innovation and business model innovation in the digital economy. A key theme is the provision of an integrated perspective to bridge the gap between innovation management and communication management at both strategic and operational levels. This book makes an important contribution to this evolving academic domain by providing multiple perspectives on latest research on innovation communication and strategic open innovation. It also provides guidance for managers to understand the diverse pathways by which they can leverage communication to shape and accelerate innovation and growth.>.
Keywords: Technological innovations -- Management.; Strategic planning.; Business communication.; elektronické knihy; electronic books